Pengembangan Instrumen Penilaian Kemampuan Berpikir Kronologis Menggunakan Aplikasi Kahoot di Kelas XI SMA - Lili Sulita Putri; Aisiah Aisiah (Lembaga Yasin AlSys, 2026)
This study was motivated by the suboptimal use of assessment instruments in history learning that can systematically measure students’ chronological thinking ability. This study aimed to identify the design stages, measure the feasibility, test the practicality, and evaluate the effectiveness of a Kahoot-assisted chronological thinking assessment instrument. This study used a Research and Development (R&D) method with the ADDIE model. The data collection instruments consisted of feasibility validation sheets completed by two subject matter experts and one evaluation expert, practicality test questionnaires completed by one history teacher and 36 Phase F Grade XI students at SMA Negeri 1 Sijunjung, and test items to measure the effectiveness of the chronological thinking assessment instrument. The feasibility test results showed that the developed chronological thinking assessment instrument was classified as highly feasible based on the assessment of the subject matter experts, with an average score of 3.75, and the evaluation expert, with an average score of 3.44. The practicality test results showed that the instrument was classified as highly practical based on the teacher’s assessment, with an average score of 3.67, and the students’ assessment, with an average score of 3.35. The effectiveness test through testing showed that the students’ average chronological thinking ability was in the high category, with a score of 79.33. Thus, the Kahoot-assisted chronological thinking ability assessment instrument was declared feasible, practical, and effective for use in history learning at SMA Negeri 1 Sijunjung. These findings imply the availability of an alternative digital assessment instrument that can support the measurement of chronological thinking ability more interactively in history learning.